Low risk of recurrence following artesunate-Sulphadoxine-pyrimethamine plus primaquine for uncomplicated Plasmodium falciparum and Plasmodium vivax infections in the Republic of the Sudan - Hamid, MMA; Thriemer, K; Elobied, ME; Mahgoub, NS; Boshara, SA; Elsafi, HMH; Gumaa, SA; Hamid, T; Abdelbagi, H; Basheir, HM; Marfurt, J; Chen, I; et al. (BioMed Central, 2018)
Background First-line schizontocidal treatment for uncomplicated malaria in the Republic of the Sudan is artesunate (total dose 12 mg/kg) plus Sulphadoxine/pyrimethamine (25/1.25 mg/kg) (AS/SP). Patients with Plasmodium vivax are also treated with 14 days primaquine (total dose 3.5 mg/kg) (PQ). The aim of this study was to assess the efficacy of the national policy. Methods Patients above 1 year, with microscopy-confirmed, Plasmodium falciparum and/or P. vivax malaria were treated with AS/SP. Patients with P. falciparum were randomized to no primaquine (Pf-noPQ) or a single 0.25 mg/ kg dose of PQ (Pf-PQ1). Patients with P. vivax received 14 days unsupervised 3.5 mg/kg PQ (Pv-PQ14) on day 2 or at the end of follow up (Pv-noPQ). Primary endpoint was the risk of recurrent parasitaemia at day 42. G6PD activity was measured by spectrophotometry and the Accessbio Biosensor™. Results 231 patients with P. falciparum (74.8%), 77 (24.9%) with P. vivax and 1 (0.3%) patient with mixed infection were enrolled. The PCR corrected cumulative risk of recurrent parasitaemia on day 42 was 3.8% (95% CI 1.2–11.2%) in the Pf-noPQ arm compared to 0.9% (95% CI 0.1–6.0%) in the Pf-PQ1 arm; (HR = 0.25 [95% CI 0.03–2.38], p = 0.189). The corresponding risks of recurrence were 13.4% (95% CI 5.2–31.9%) in the Pv-noPQ arm and 5.3% (95% CI 1.3–19.4%) in the Pv-PQ14 arm (HR 0.36 [95% CI 0.1–2.0], p = 0.212). Two (0.9%) patients had G6PD enzyme activity below 10%, 19 (8.9%) patients below 60% of the adjusted male median. Correlation between spectrophotometry and Biosensor™ was low (rs = 0.330, p < 0.001). Conclusions AS/SP remains effective for the treatment of P. falciparum and P. vivax. The addition of PQ reduced the risk of recurrent P. falciparum and P. vivax by day 42, although this did not reach statistical significance. The version of the Biosensor™ assessed is not suitable for routine use.